Mitch Rapp : Capture or Kill - Book 23 - Flynn, Vince; Bentley, Don (Thorndike, Maine : Center Point Large Print, 2024)
Azad Ashani tries to thwart an Iranian plot that could trigger a catastrophic conflict in the Middle East while CIA Director Irene Kennedy races to confirm Osama bin Ladens location.
Keywords: Rapp, Mitch -- (Fictitious character) -- Fiction; Bin Laden, Osama, -- 1957-2011 -- Fiction; United States. -- Central Intelligence Agency -- Fiction; Intelligence officers -- Fiction; Terrorism -- Middle East; Fiction; Historical fiction; Thrillers (Fiction); Novels; Large print books